Faktor Penentu dan Pendorong Keputusan Berkunjung Wisatawan di Desa Wisata - Lanang Smesta, Bagas; Dwi Hadian, Mohamad Sapari (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
The growth of tourism villages has become a key strategy for addressing challenges faced by the tourism industry during the pandemic. It's playing a big role in boosting Indonesia’s creative economy. This research focuses on identifying what drives tourists to visit these villages and which factors are most important in their decision-making. By reviewing various studies, key factors emerged: tourism product attribute (attraction, amenities, accessibility), tourist services, location, how easy it is to get there, and the impact of electronic word-of-mouth (e-WoM). Results showed that the main factors influencing tourists' choices were the attractions themselves and e-WoM. These insights can help village managers fine-tune their marketing efforts. Additionally, understanding that tourists often look for an escape from their daily routines or seek relaxation can help in designing more attractive travel packages. This research adds to existing academic discussions by offering a detailed look at what influences tourist choices in rural tourism, especially in Indonesia. Future studies should look at broader databases and include international perspectives to enrich the knowledge around global practices for tourism villages.